Macrovoids suppression in Polyetherimide (PEI) hollow fibre membranes by optimizing the air gap - Oh , P.C. (2016)
Asymmetric polyetherimide (PEI) hollow fibre membranes have been prepared by dry-wet phase inversion method in which N-methyl-2-pyrrolidone (NMP) was used as solvent whereas water was used as both internal and external solvent. The polymer dope solution contained 25 wt. % of PEI and was spun at different air gaps at ambient conditions. The air gap effect was analyzed based on the surface morphology of the membranes using scanning electron microscopy (SEM). At longer air gaps, due to the dominant dry processes, finger-like pores extended to the outer skin layer and larger macrovoids appeared under the skin layer which may result in poor separation performance. The wet process presided as air gap was reduced to zero, and the instant solidification created macrovoids under the outer skin layer. At 15 and 20 cm air gaps, optimum results were obtained with minimum macrovoids and uniform finger-like pores under the thin skin layer.